Aporias of national cinema?. IN On the “end” of national cinema in the Philippines - a roundtable discussion [column] - Manzanilla, John Paul S. (2017)
Access online through this link: https://www.plarideljournal.org/article/aporias-national-cinema
Keywords: Motion pictures; Motion picture industry; Film criticism